Modeling the drainage facilities operation at the prospective construction site on the Dnipro floodland - Tymoshchuk, V.; Sherstiuk, Ye.; Niedbalski, Z.; Morozova, Т. (Розробка родовищ, 2017)
Purpose. To carry out predictive assessment of the hydrodynamic regime at the prospective construction site on the Dnipro floodland in order to choose an expedient drainage system and substantiate the drainage parameters. Findings. The main mode-forming factors of the investigated territory have been determined using the results of analysis and generalization of the data related to geological structure and hydrogeological conditions. The general hydrodynamic scheme of the simulated area has been developed, the structure of geofiltration model has been justified, its initial and boundary conditions have been determined. Predictive estimation of groundwater level regime has been executed, comparative analysis of vertical and bed drainage efficiency with various schemes of drainage element layouts has been carried out by simulation. The efficiency of the drainage structures operation in the protected area has been estimated for high-level flood conditions at the set water level in the Dnipro. Мета. Прогнозна оцінка гідродинамічного режиму підземних вод на ділянці перспективної забудови заплавної частини долини р. Дніпро у зв’язку з вибором доцільної системи дренажу та обґрунтуванням параметрів дренажного водозниження. Результати. Визначені основні режимоутворюючі фактори досліджуваної території, розроблена загальна гідродинамічна схема модельованої області й обґрунтована структура геофільтраційної моделі, визначені її початкові та граничні умови. За даними моделювання виконана прогнозна оцінка рівневого режиму підземних вод, проведено порівняльний аналіз ефективності пластового та вертикального дренажів при різних схемах компоновки водознижуючих споруд. Ефективність роботи дренажних споруд на території, що захищається, оцінена для умов проходження високого паводку при заданій забезпеченості рівня води у р. Дніпро. Цель. Прогнозная оценка гидродинамического режима подземных вод на участке перспективной застройки пойменной части долины р. Днепр в связи с выбором целесообразной системы дренажа и обоснованием параметров дренажного водопонижения. Результаты. Определены основные режимообразующие факторы исследуемой территории, разработана общая гидродинамическая схема моделируемой области и обоснована структура геофильтрационной модели, определены ее начальные и граничные условия. По данным моделирования выполнена прогнозная оценка уровенного режима подземных вод, проведен сопоставительный анализ эффективности пластового и вертикального дренажей при различных схемах компоновки водопонизительных сооружений. Эффективность работы дренажных сооружений на защищаемой территории оценена для условий прохождения высокого паводка при заданной обеспеченности уровня воды в р. Днепр.